2019
DOI: 10.1038/s41573-019-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism as a common therapeutic target in cancer, neurodegeneration and beyond

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
897
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,025 publications
(921 citation statements)
references
References 288 publications
15
897
0
9
Order By: Relevance
“…The metabolism of tryptophan might be the most complicated one among AAs, and was involved in the regulation of immunity, neuronal function and intestinal homeostasis [44]. Majority (~95%) of absorbed tryptophan degraded via kynurenine pathway, in which IDOs and tryptophan-2,3-dioxygenase (TDO) were the main rate-limiting enzymes.…”
Section: Tryptophan Is the Least Used And Available Eaamentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of tryptophan might be the most complicated one among AAs, and was involved in the regulation of immunity, neuronal function and intestinal homeostasis [44]. Majority (~95%) of absorbed tryptophan degraded via kynurenine pathway, in which IDOs and tryptophan-2,3-dioxygenase (TDO) were the main rate-limiting enzymes.…”
Section: Tryptophan Is the Least Used And Available Eaamentioning
confidence: 99%
“…Besides the usage for protein synthesis, a small fraction of tryptophan was catabolized by tryptophan hydroxylase (TPH) for the production of serotonin (5-hydroxytryptophan, 5-HT) and melatonin. Tryptophan and its metabolites were used and catabolized by various organs and cells to further generate bioactive metabolites, including neuroprotective kynurenic acid by astrocytes, neurotoxic quinolinic acid by microglia, neuromodulator tryptamine, immune suppressive metabolites (such as 3hydroxykynurenine, 3-hydroxyanthranilic acid and xanthurenic acid) [42,44]. The catabolism of tryptophan induced by IFN-γ in cancer cells and macrophages showed that the catabolites of tryptophan differed in kynurenine, anthranilic acid and 3-hydroxyanthranilic acid [40].…”
Section: Tryptophan Is the Least Used And Available Eaamentioning
confidence: 99%
“…In fact, enhanced Trp breakdown, reflected by decreased Trp and elevated kynurenine (Kyn) concentrations in the peripheral blood, is often observed in cancer patients and related to tumor progression, poor clinical outcome ( Table 1) and an impaired quality of life (QoL) (58,85). Trp breakdown in patients with malignancies is primarily mediated by increased tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase 1 (IDO1) activities (86). The latter is primarily activated by proinflammatory cytokines of the T helper 1 (Th1) type immune response, particularly interferon gamma (IFN-γ) (87).…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocal interactions between metabolic pathways and immunity coordinate cross-talk between whole-body and immune cell functions and is involved in a variety of health and disease states (39). Among these pathways, metabolism of L-Tryptophan (Trp), one of the nine essential amino acid that is obtained exclusively from dietary intake in humans, regulates immune responses at multiple levels (40).…”
Section: Ido1 In Immune Regulationmentioning
confidence: 99%
“…Altogether these data suggest that IDO1 induction can control the host immune response and promote tolerance induction in several different contexts. Accordingly, dysregulation of Trp metabolism have been reported in various diseases including tumors, autoimmunity, and neurodegenerative diseases (40). Specifically, in different in vivo models, IDO1 expression has shown to have a protective effect on autoimmune encephalitis and pancreatic islet allograft (64,68).…”
Section: Ido1 In Immune Regulationmentioning
confidence: 99%